2011
DOI: 10.1158/1535-7163.mct-10-1050
|View full text |Cite
|
Sign up to set email alerts
|

Dependence on the MUC1-C Oncoprotein in Non–Small Cell Lung Cancer Cells

Abstract: Non-small cell lung cancer (NSCLC) cells are often associated with constitutive activation of the phosphatidylinositol 3-kinase (PI3K)->Akt->mTOR pathway. The mucin 1 (MUC1) heterodimeric glycoprotein is aberrantly overexpressed in NSCLC and induces gene signatures that are associated with poor survival of NSCLC patients. The present results demonstrate that the MUC1 C-terminal subunit (MUC1-C) cytoplasmic domain associates with PI3K p85 in NSCLC cells. We show that inhibition of MUC1-C with cell-penetrating p… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

5
192
0

Year Published

2012
2012
2022
2022

Publication Types

Select...
8
1

Relationship

3
6

Authors

Journals

citations
Cited by 146 publications
(200 citation statements)
references
References 46 publications
(89 reference statements)
5
192
0
Order By: Relevance
“…Cells were treated with the MUC1-C inhibitor GO-203 ([R] 9 -CQCRRKN) or the inactive control peptide CP-2 ([R] 9 -AQARRKN). 29 Cells were also treated with the b-catenin inhibitor JW67 30 or vehicle control dimethylsulfoxide (DMSO).…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…Cells were treated with the MUC1-C inhibitor GO-203 ([R] 9 -CQCRRKN) or the inactive control peptide CP-2 ([R] 9 -AQARRKN). 29 Cells were also treated with the b-catenin inhibitor JW67 30 or vehicle control dimethylsulfoxide (DMSO).…”
Section: Methodsmentioning
confidence: 99%
“…26,38 Accordingly, we developed agents, such as the cell-penetrating peptide , that target the CQC motif and block MUC1-C homodimerization ( Figure 1C). 29,39 Treatment of RPMI8226 cells with GO-203, but not with the control peptide CP-2 ( Figure 1C), resulted in the downregulation of MUC1-C expression ( Figure 1D). We also found that suppression of MUC1-C is associated with decreases in MYC mRNA and protein ( Figure 1D, left and right).…”
Section: Muc1-c Induces Myc Expression In MM Cellsmentioning
confidence: 99%
“…4,5 Cancer-associated MUC1 is involved in abnormal interactions with receptor tyrosine kinases and other cell surface receptors. These abnormal interactions trigger inappropriate activation of intracellular signalling pathways and thus promote the growth, proliferation, and survival of cancer cells.…”
Section: Introductionmentioning
confidence: 99%
“…[26][27][28] In particular, MUC1-C inhibitor treatment of MM cells growing in vitro and as tumor xenografts is associated with inhibition of growth and induction of late apoptosis/ necrosis.…”
mentioning
confidence: 99%